SIMULTANEOUS SURGICAL TREATMENT OF STOMACH CANCER AND JEJUNAL DIVERTICULOSIS - R.Z. YULDOSHEV; А.А. KHODZHAMKULOV; D.SH. NURALIEV; D.SH. NURALIEV; A.SH. ABDULLOEV (Avicenna Tajik State Medical University, 2021)
The article presents a case of a combination of stomach cancer and jejunal diverticulosis in a 71-year-old female patient. Stomach cancer was diagnosed preoperatively both clinically and by instrumental (endoscopic and radiological) and pathomorphological methods. During the surgery, jejunal diverticulosis was accidentally revealed. Considering the stomach cancer resectability and the presence of diffuse intestinal diverticulosis, resection of the proximal jejunum, distal subtotal gastrectomy, Roux-en-Y gastroenteroanastomosis, and D2 lymphadenectomy were performed. The immediate postoperative period was complicated by perforation of the anterior wall of the resected stomach, and defect was urgently sutured. Control X-ray examination showed that both the stomach and gastroenteroanastomosis were normal, the passage of contrast through the jejunum was satisfactory. The patient was discharged home on the 12th day in satisfactory condition.